The G Protein-Coupled Bile Acid Receptor, TGR5, Stimulates Gallbladder Filling - Li, Tingting (Endocrine Society, 2011)
TGR5 is a G protein-coupled bile acid receptor present in brown adipose tissue and intestine, where its agonism increases energy expenditure and lowers blood glucose. Thus, it is an attractive drug target for treating human metabolic disease. However, TGR5 is also highly expressed in gallbladder, where its functions are less well characterized. Here, we demonstrate that TGR5 stimulates the filling of the gallbladder with bile. Gallbladder volume was increased in wild-type but not Tgr5(−/−) mice by administration of either the naturally occurring TGR5 agonist, lithocholic acid, or the synthetic TGR5 agonist, INT-777. These effects were independent of fibroblast growth factor 15, an enteric hormone previously shown to stimulate gallbladder filling. Ex vivo analyses using gallbladder tissue showed that TGR5 activation increased cAMP concentrations and caused smooth muscle relaxation in a TGR5-dependent manner. These data reveal a novel, gallbladder-intrinsic mechanism for regulating gallbladder contractility. They further suggest that TGR5 agonists should be assessed for effects on human gallbladder as they are developed for treating metabolic disease.